Alicyclobacillus spoilage and control - a review - Pornpukdeewattana, Soisuda; Jindaprasert, Aphacha; Massa, Salvatore (My University, 2020)
In the last few decades Gram positive non pathogenic, rod shaped, thermo-acidophilic and acid-tolerant spore-forming bacteria such as Alicyclobacillus spp. have been identified as the causative agent in spoilage of commercially pasteurized fruit juice. In particular, A. acidoterrestris is considered a major producer of off-flavors. The spores of A. acidoterrestris possess the ability to survive commercial pasteurization processes, to germinate and grow in low pH environments and to produce volatile, unpleasant odorous compound (guaiacol) in fruit juices. The flat sour type of spoilage (without gas production or package swelling) is characterized as having a “medicinal,” “smoky,” and “antiseptic” off-flavor and makes the final juice product unacceptable. Spoilage by Alicyclobacillus is a major concern for producers since many of the new methods, which can destroy spores in the absence of chemical additives, may not destroy Alicyclobacillus. Although A. acidoterrestris is not pathogenic to humans, it can result in significant economic losses to juice processors because of its odor. The present review includes the taxonomy of Alicyclobacillus spp., their general characteristics, their resistance to heat and possible off-flavor production pathways. Particular emphasis is given to commonly used control measures, including physical, chemical and biological treatments currently available for removal of Alicyclobacillus spp.
Keywords: Alicyclobacillusspp; control; fruit juices; spoilage; Thermo-acidophilic spore-forming bacteria